Manajemen Konflik dalam Komunikasi Remaja dengan Orang Tua Sebagai Upaya Impementasi Hadis Birrul Walidain - Siti Aminah; Muliyadi Saputra Rambe (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2024)
This research aims to find out how conflict is managed in communication between parents and children, and what a child's motivation is in managing this conflict. This research is quantitative and qualitative research using the literature study method as an analytical tool. Based on the research that has been carried out, it was found that firstly there are many hadiths about Birrul Walidain, secondly there are several conflicts in daily communication between children (adolescents) and their parents, some of whom can solve their problems and also some of them who cannot solve their problems so they try to run away from the problems that cause him to get involved in these problems. Third, the conflict turns out to have a negative impact on both parties, both the children and the parents. Fourth, management in resolving conflicts with parents, namely by using the mubjadi method